Synthesis of context‐aware business‐to‐business processes for location‐based services through choreographies. Issue 10 (13th December 2021) - Filippone, Gianluca; Autili, Marco; Tivoli, Massimo
Abstract: Modern technologies and emerging wireless communication solutions in the Information and Communications Technology (ICT) world are empowering the spread of the most disparate ready‐to‐use software services distributed over the globe and accessed by an increasing number of users. This state of affairs encourages the development of systems based on the reuse of existing services through composition approaches, notably choreographies. Also Public Administrations are driven towards a digitalization process which exploits composition approaches to build complex and interoperable systems that can be remotely accessed by citizens and authorities. However, an automatic support is needed in order to realize the service composition and the distributed coordination logic that enforces the correct choreography realization. Moreover, the need for building dynamic and user‐centered systems calls for the realization of choreographies capable to adjust their behavior to the surrounding context. This work presents our proposal for addressing the choreography realization problem, by describing an automated process for the synthesis of choreography‐based systems. The synthesized systems are location‐aware and able to adapt the services' interaction according to the user's needs and context conditions. We show and evaluate our approach at work on a real use case scenario in the Public Administration domain. Abstract : This work presents a proposal for addressing the choreography realization problem, by describing an automated process for the synthesis of context‐aware choreography‐based business‐to‐business applications. The synthesized systems are able to adapt the services' interaction according to the user's needs and runtime context conditions. We show and evaluate our approach at work on a real use case scenario in the Public Administration domain, in which location‐based services are composed together in a choreography.